Innovative Integrated Disaster Education in Physics Learning: An Effort to Enhance Students’ Disaster Literacy Skills - Saregar, Antomi; Putra, Fredi Ganda; Diani, Rahma; Anugrah, Adyt; Misbah, Misbah; Umam, Rofiqul (Universitas Negeri Semarang, 2025)
Disaster-prone regions require an education system that equips students with both scientific understanding and disaster preparedness. However, integration of disaster mitigation content into subject-specific learning, particularly physics, remains limited. This study aims to develop and evaluate the effectiveness of physics teaching materials integrated with disaster mitigation education to enhance students’ disaster literacy skills. A mixed-method approach with an exploratory sequential design was employed. The development process followed the 4D model (Define, Design, Develop, and Disseminate) to systematically design and implement teaching materials. The study was conducted in two high schools in South Lampung Regency, Lampung, Indonesia involving four classes (two experimental and two control groups) with a total of 128 students, consisting of 63 students in the experimental groups and 65 in the control groups. The T-test results show that the use of disaster mitigation-based teaching materials had a statistically significant effect on students' disaster literacy abilities, with a significance value of 0.000 (p < 0.05). Furthermore, the results of the effect size analysis (Cohen’s d = 0.62 and 0.66) fall within the moderate category, confirming that this intervention had a significant impact on enhancing students’ disaster literacy skills related to disaster mitigation. The implementation of this teaching material not only enhances students’ understanding of physics concepts but also increases their awareness and preparedness for disasters, particularly around disaster literacy, making it a strategic innovation in disaster education. This research contributes significantly to the development of disaster education curricula in Indonesia, particularly within the context of physics education.